Environmental Issues in Automotive Industry - Golinska, Paulina (EcoProduction, Environmental Issues in Logistics and Manufacturing,, 2014)
The automotive industry is one of the most environmental aware manufacturing sectors.  Product take-back regulations influence design of the vehicles, production technologies but also the configuration of automotive reverse supply chains. The business practice comes every year closer to the closed loop supply chain concept which completely reuses, remanufactures and recycles all materials.  The book covers the emerging environmental issues in automotive industry through the whole product life cycle.  Its focus is placed on a multidisciplinary approach. It presents viewpoints of academic and industry personnel on the challenges for implementation of sustainable police in the automotive sector.